CELL CHARACTERIZATION: PRINCIPLES AND TECHNIQUES OF MICROSCOPY, FLOW CYTOMETRY AND IMMUNOFLUORESCENCE - Maranduba, Carlos Magno da Costa; Silva, Fernando de Sá (Seven Editora, 2025)
This chapter aimed to present the two main techniques for cellular study: optical, immunofluorescence, and confocal microscopy, and flow cytometry. Both have specific techniques for sample preparation, but all are based on immunological or immunocytochemical methods. The chapter explains the operating principles of these two instruments and their variations, as well as the principles of immunological techniques and fluorescence. It also presents concepts and methods for preparing immunocytochemistry samples, along with all the preceding procedures on how different types of antibodies are produced and which should be selected for each purpose—whether for cell surface, intracellular, or organelle and nuclear labeling. At the end of each technique, the reagents to be used and their preparation methods are presented. DOI: https://doi.org/10.56238/sevened2025.036-047